the Difficulties in teaching - learning statistics and probability: A student perspective. - Alvarez, Nevy; Rivadeneira Flores, Jaime Oswaldo; Montero Zambrano, Sonia Del Pilar (Revista Ecos de la Academia, 2023)
The teaching of statistics and probability in Ecuadorian high school is based on the development of skills focused on the resolution and interpretation of problems, which currently faces difficulties by showing low results in the evaluations at the end of secondary education. The objective of this research is to identify the difficulties faced by the teaching-learning process of statistics and probability to assess the state of secondary education in the canton of Ibarra, province of Imbabura - Ecuador. This is a quantitative research of descriptive-correlational and cross-sectional nature; the population studied was 362 students through a previously elaborated survey. Through the Chi-square hypothesis test it was found that there is a relationship between cognitive learning difficulties and the didactics applied by the teachers (p0.05). It is concluded that cognitive learning difficulties are presented by the application of traditional teaching methods and techniques that trigger superficial knowledge.
Keywords: Statistics and probability, teaching, learning, didactics, difficulties.